Comparison of Maternal and Infant Outcomes Between the First and Second Pregnancies in Women With Pregestational Diabetes - Sayoko Tanaka; Keiko Yanagisawa; Tomoko Suzuki; Jun Kakogawa; Tetsuya Babazono (Tokyo Women's Medical University Journal, 2023)
Background: The effect of parity on adverse pregnancy outcomes is well established in healthy pregnant women; however, the influence of parity on pregnancy outcomes in women with diabetes remains poorly understood. Therefore, we examined the association between parity and glycemic control, as well as pregnancy outcomes, in women with pregestational diabetes. Methods: A retrospective observational study was conducted on 59 women with diabetes, including 43 with type 1 diabetes and 16 with type 2 diabetes, who had a second pregnancy. Maternal clinical characteristics and pregnancy outcomes were compared between the first and second pregnancies. Results: The second pregnancy was characterized by higher pre-pregnancy body weight, increased insulin requirements, and poorer glycemic control during the third trimester. The first pregnancy was associated with a higher prevalence of diabetic retinopathy deterioration and hospitalization for glycemic control. No significant differences were observed in the perinatal or neonatal complications between the first and second pregnancies, except for hypertensive disorders of pregnancy, which were more common in the first pregnancy. Conclusions: Our findings emphasize the need for increased vigilance for maternal complications during the first pregnancy, weight control between pregnancies, and appropriate adjustment of insulin dosage during subsequent pregnancies in women with diabetes.